(untitled) (Bangladesh Journal of Medical Science, 2012)
Objective: A study was carried out to know the overall prevalence of various causes responsible for cervical lymphadenopathy of more than 3 weeks duration. FNAC has been evaluated as a diagnostic tool in our clinical set up. We aimed to present 120 cases which we treated in our center within last 4 years. Methods: A retrospective study has been carried out from August 2007 to August 2011 in the department of Otolaryngology and Head-Neck Surgery at CMH Rangpur, Apollo Hospitals Dhaka And Ibn Sina Medical College Hospital Dhaka. All patients presented with cervical lymphadenopathy of more than 3 weeks duration. FNAC has been done for all suspected cases. CT neck has been done in 4 cases for deep jugular nodes. 60 patients underwent lymph node biopsy as FNAC report was non-specific lymphadenitis. For three cases we have done frozen section biopsy. Preoperative workup with routine blood tests, Xray chest and tuberculin tests have been carried out for all cases. Results: Out of 120 FNAC of cervical lymphadenopathy - 60 were non-specific lymphadenitis, 34 were tuberculosis, 13 were metastatic (with 2 occult primary), 7 were lymphomas (Immunocytochemistry proved ) and 6 were abscess. All 60 non-specific lymphadenopathy cases (FNAC report) underwent lymph node biopsy.5 cases were consistent with tuberculosis , 1 was lymphoma and rest were reactive . For 3 cases frozen section biopsy have been done. One was consistent with granulomatous disease and two cases were diagnosed as lymphoid hyperplasia. Both the lymphoid hyperplasia cases have been diagnosed as Castleman’s disease after histopathology report. Conclusion: The study concluded the fact that the non-specific infection is the most common cause of cervical lymphadenopathy followed by tuberculosis .Supplemented with routine laboratory investigations, FNAC give very important clue to the physicians that can be routinely used in patients with cervical lymphadenopathy. DOI: http://dx.doi.org/10.3329/bjms.v11i1.9818 BJMS 2012; 11(1): 25-27